Investigations on the Internal Calibration of Multi-Channel SAR - Younis, M.; Rommel, T.; De Almeida, F.; Huber, S.; Martone, M.; Villano, M.; Krieger, Gerhard (IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2017)
In this paper the calibration methods of state-of-the-art spaceborne SAR are reviewed to suggest calibration strategies for future SAR systems. These systems will utilize digital beamforming, which poses new challenges for the calibration, as the increased complexity of multi-channel SAR does not allow for the extrapolation of current calibration techniques. Further, depending on the DBF operation mode, real-time error measurement and correction is unavoidable, which requires a reconsideration to current calibration approaches. One the other hand, the digital hardware already present in multi-channel SAR systems offer completely new opportunities for the calibration such as on-board error correction and digital calibration. This requires a reconsideration of the calibration strategy for spaceborne SAR, as presented in the paper.
DLR Import::2019-04-03
Keywords: Calibration; Internal SAR Calibration; Multi-Channel Calibration; SAR Internal Errors